EFFECT OF WATER AND ORGANIC FERTILIZER MANAGEMENTS ON SOIL REDOX POTENTIAL, NITROGEN UPTAKE, AND RICE PERFORMANCES UNDER SYSTEM OF RICE INTENSIFICATION - , RIZKI MAFTUKHAH; , Prof. Dr. Ir. Sigit Supadmo Arif, M.Eng. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Water and fertilizer managements on rice production system affected the change of nutrient availability of soil and rice yield. Regarding on water scarcity, high fertilizer cost, and negative environmental impacts due to high agrochemicals, itâs necessary to improve resource use efficiency on rice cultivation. Recently, system of rice intensification (SRI) is the recommendations which use intermittent irrigation, single seedlings, early transplanting, wide spacing, and organic fertilizer. The aims of this study are to learn the effect of different water and organic fertilization managements on soil chemical properties (redox potential, total nitrogen, and available iron) and rice performances. We also develop a simple model of nitrogen uptake by rice plant via water balance. Pot experiments were conducted under SRI framework with continuous flooding (CF), intermittent (IT), and field capacity (FC) irrigation